Insect pests of potato : global perspectives on biology and management - Alyokhin, Andrei; Vincent, Charles, 1953-; Giordanengo, Philippe; ScienceDirect eBooks (London ; Waltham, MA : Elsevier / Academic Press, 2013)
Insect Pests of Potato: Biology and Management provides a comprehensive source of up-to-date scientific information on the biology and management of insects attacking potato crops, with an international and expert cast of contributors providing its contents. This book presents a complete review of the scientific literature from the considerable research effort over the last 15 years, providing the necessary background information to the subject of studying the biology management of insect pests of potatoes, assessment of recent scientific advances, and a list of further readings. This comprehensive review will be of great benefit to a variety of scientists involved in potato research and production, as well as to those facing similar issues in other crop systems. Written by top experts in the field, this is the only publication covering the biology, ecology and management of all major potato pests. Emphasizes ecological and evolutionary approaches to pest management. Summarizes information from hard-to-get publications in China, India, and Russia.
Includes bibliographical references and index.
Title from publisher's Web site; (ScienceDirect, viewed on Aug. 9, 2012).
Elsevier
Keywords: Potatoes -- Diseases and pests; Potatoes -- Diseases and pests; Electronic books